Composite sheet
By uniformly distributing MOF within a fiber-based sheet base material through impregnation and heat treatment, the method addresses the issue of surface-only MOF support, enhancing gas adsorption performance and flexibility.
Patent Information
- Application Number
- JP2024100986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-06-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-24
AI Technical Summary
Existing methods for supporting metal-organic frameworks (MOFs) on nonwoven fabrics result in MOF particles predominantly remaining on the surface without penetrating into the fabric, limiting gas adsorption performance.
A method involving impregnation of metal ions and organic ligands into a sheet base material made of fibers, followed by heat treatment, to uniformly distribute and support MOF throughout the fabric, ensuring high mass ratio and surface coverage.
The method enables a composite sheet with enhanced gas adsorption performance by uniformly distributing MOF within the fabric, maintaining high surface exposure and reducing dropout, while ensuring flexibility and air permeability.
Smart Images

Figure 2025013207000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite sheet in which a metal-organic framework is supported on a sheet substrate. [Background technology]
[0002] Metal organic frameworks (MOFs) have attracted attention as high-performance gas adsorption materials because of their uniform pore size, high specific surface area, and high separation performance. However, MOFs are known to be difficult to handle as individual particles because they are fine powders on the micron scale. In response to this, a technology is known that supports MOFs on a substrate such as a nonwoven fabric, making it possible to handle a large amount of MOFs at once (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-191913 A [Patent Document 2] China Patent Application Publication No. 112002938 [Patent Document 3] China Patent Application Publication No. 109881483 Summary of the Invention [Problem to be solved by the invention]
[0004] In order to improve gas adsorption performance, it is necessary to support many MOFs on the nonwoven fabric. To achieve this, it is advantageous to support MOFs not only on the surface layer of the nonwoven fabric but also inside the fabric. However, when using common methods such as scattering MOF particles on the nonwoven fabric or impregnating the nonwoven fabric with a MOF dispersion, the MOF particles tend to remain on the surface layer of the nonwoven fabric without penetrating into the interior of the fabric.
[0005] An object of the present invention is to provide a composite sheet having a high gas adsorption performance, in which a metal-organic framework is supported in a sheet base material composed of fibers. [Means for solving the problem]
[0006] In a composite sheet according to one embodiment of the present invention, a metal organic framework is dispersed in a sheet base material made of fibers. In one embodiment, the metal-organic framework is supported on the surface of the fiber. In one embodiment, the ratio of the mass of the metal organic framework to the total mass of the composite sheet is 80 mass % or more. In one embodiment, the surface coverage by the metal-organic framework of the fibers constituting the central portion in the thickness direction of the composite sheet is 60% or more. In one embodiment, the metal organic framework has a surface exposure rate of 50% or more.
[0007] In a method for producing a composite sheet according to one embodiment of the present invention, a composite sheet is produced in which a metal organic framework is supported in a sheet base material made of fibers. In one embodiment, a first raw material solution containing one of metal ions and organic ligands that are raw materials for the metal organic framework, and a second raw material solution containing the other are prepared. In one embodiment, the sheet substrate is impregnated with the first raw material solution. In one embodiment, the sheet base material is impregnated with the second raw material solution before the first raw material solution with which the sheet base material has been impregnated is dried. In one embodiment, the sheet substrate impregnated with the second raw material solution is dried. In one embodiment, the dried sheet substrate is subjected to a heat treatment. In one embodiment, the ratio of the mass of the metal organic framework to the mass of the entire composite sheet after the heat treatment is 80 mass% or more, impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; The sheet substrate impregnated with the second raw material solution is dried. Repeat the process. Effect of the Invention
[0008] According to the present invention, a metal-organic framework is supported in a sheet base material made of fibers, and a composite sheet having high gas adsorption performance can be provided. [Brief description of the drawings]
[0009] [Figure 1] 1 is a microstructure photograph of a cross section of a composite sheet taken by SEM. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a fiber constituting a composite sheet. [Diagram 3] 2 is a flowchart showing a method for manufacturing a composite sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Basic composition of composite sheet] A composite sheet according to one embodiment of the present invention has a sheet substrate and a metal organic framework (MOF). The sheet substrate of the composite sheet according to this embodiment is a substrate formed into a sheet shape from fibers, and is typically a nonwoven fabric, but may also be a woven fabric, knitted fabric, mesh, or the like. The MOF of the composite sheet according to this embodiment is typically a fine powder composed of metal ions and organic ligands, dispersed in the sheet substrate, and supported on the surface of the fibers that compose the sheet substrate. Although such structures are sometimes called porous coordination polymers (PCPs), this specification will refer to them unified as metal-organic frameworks (MOFs).
[0011] Each MOF particle used in the composite sheet of this embodiment is typically porous with numerous pores of uniform diameter, and functions as a gas adsorption material by adsorbing and retaining gas molecules in each pore. The composite sheet of this embodiment is a gas adsorption sheet that is configured so that a large number of MOFs are supported on a sheet substrate in a state in which they can effectively exhibit their gas adsorption performance, thereby enabling the MOFs supported on the sheet substrate as a whole to adsorb a large amount of gas. 1 and 2 show an example of a state in which MOFs are supported on the fibers of the sheet substrate in the composite sheet according to this embodiment. In the microstructure photograph shown in FIG. 1 taken by a scanning electron microscope (SEM), the cross section of the fiber is shown, and it is possible to confirm that the surface of the fiber is covered with MOFs. As shown in FIG. 2, it is preferable that most of the surface of the fiber is covered with MOFs. In the example shown in FIG. 2, MOFs are immobilized on the fiber surface in a single layer, but MOFs may be laminated across multiple layers.
[0012] In the composite sheet according to this embodiment, a layer of MOFs is typically formed on the surface of the fibers. Here, the MOF layer refers to a state in which an aggregate of MOF particles forms a layer as a whole. Specifically, the MOF layer includes one or more of the following forms: a state in which a plurality of fine powder or particulate MOFs are deposited or laminated on the surface of a fiber, a state in which fine powder or particulate MOFs are generated and grow on the surface of a fiber to cover the surface of the fiber, and a state in which adjacent MOF particles are integrated as they are generated and grow to cover the surface of the fiber as an integrated film. In the composite sheet according to this embodiment, the particle size of the MOF may be larger or smaller than the fiber diameter of the sheet substrate.
[0013] The MOFs available for the composite sheet according to this embodiment have various pore sizes depending on the combination of metal ions and organic ligands. Therefore, in the composite sheet according to this embodiment, the pore size of the MOF supported on the sheet substrate can be determined according to the molecular size of the gas to be adsorbed. As a result, in the composite sheet according to this embodiment, the MOF supported on the sheet substrate can selectively adsorb a specific gas.
[0014] In the composite sheet according to this embodiment, for example, by using MOFs capable of selectively adsorbing carbon dioxide, it becomes possible to recover carbon dioxide, which is known as a greenhouse gas, and use it as a chemical raw material, etc. In addition to carbon dioxide, by using MOFs capable of selectively adsorbing, for example, hydrocarbons (methane, ethane, propane, etc.), hydrogen, hydrogen sulfide, nitrogen, oxygen, etc., the composite sheet according to this embodiment can be configured as a gas adsorption sheet compatible with these gases.
[0015] In the composite sheet according to this embodiment, the effect of the present invention can be obtained regardless of the use of any of a wide variety of MOFs. In other words, MOFs are synthesized by self-organization mainly based on coordinate bonds between metal ions and organic ligands. This reaction mechanism is the same regardless of the type of metal ion and organic ligand. Since there are, in principle, infinite combinations of metal ions and organic ligands in MOFs, the combination of MOFs has infinite possibilities. In this case, the type of metal ion, the shape, length, and substituents of the ligands can be selected and synthesized according to the type of gas to be adsorbed and the adsorption characteristics, so that the shape of the resulting nanospace can be tuned as desired. From the above, the present invention can obtain the same effect for any MOF.
[0016] [Basic structure of composite sheet manufacturing method] (Brief explanation) The basic configuration of the manufacturing method of the composite sheet according to this embodiment will be described with reference to the flow chart shown in Fig. 3. The manufacturing method of the composite sheet shown in Fig. 3 includes step S01 (preparation of raw material solution), step S02 (impregnation with first raw material solution), step S03 (impregnation with second raw material solution), step S04 (drying), and step S05 (heat treatment). Steps S01 to S05 according to this embodiment will be described below.
[0017] (Step S01: Prepare raw material solution) In step S01, a first raw material solution and a second raw material solution are prepared as raw material solutions for MOFs. The first raw material solution and the second raw material solution are solutions containing either metal ions or organic ligands that are raw materials for MOFs. These solutions are configured to mix with each other to cause a reaction between the metal ions and the organic ligands to generate MOFs. In order to increase the amount of MOF produced and improve production efficiency, the concentrations of metal ions and organic ligands in the first and second raw material solutions are preferably 0.05 mol / L or more. In order to ensure smooth production of MOFs, the concentrations of metal ions and organic ligands in the first and second raw material solutions are preferably 10 mol / L or less. In this embodiment, the first raw material solution contains metal ions as a solute, and the second raw material solution contains organic ligands as a solute. In this embodiment, the solvent of the first raw material solution preferably contains water. In this embodiment, the solvent of the second raw material solution preferably contains ethanol.
[0018] As an example of step S01, when the MOF is ELM-11 (ELM = Elastic Layer-structured Metal organic framework), the first raw material solution is Cu(BF 4 ) 2 An ethanol solution of 4,4'-bipyridine (bpy) is prepared as the second raw material solution.
[0019] (Step S02: Impregnation with the first raw material solution) In step S02, the sheet substrate is impregnated with the first raw material solution prepared in step S01. The method of impregnating the sheet substrate with the first raw material solution in step S02 is not limited to a specific method. For example, the sheet substrate can be impregnated with a sufficient amount of the first raw material solution by using one or more methods selected from the group consisting of dripping with a dropper, spraying, spray coating, die coating, curtain coating, and dip coating. Among these, it is preferable to use one or more methods selected from the group consisting of dripping with a dropper, spraying, spray coating, die coating, and curtain coating from the viewpoint of preventing the occurrence of contamination in the first raw material solution. In step S02, the time for impregnating the sheet substrate with the first raw material solution is preferably 0.01 minutes or more, more preferably 0.05 minutes or more, and even more preferably 0.1 minutes or more, from the viewpoint of penetrating the raw material solution to the center of the substrate. From the viewpoint of ensuring productivity, the time for impregnating the sheet substrate with the first raw material solution is preferably 30 minutes or less, more preferably 15 minutes or less, and even more preferably 5 minutes or less. In this embodiment, the "time for impregnating the (first or second) raw material solution" refers to the sum of the time for which the work for impregnating the sheet substrate with the raw material solution, such as dripping the raw material solution with a dropper, is performed, and the time for which the raw material solution is left to permeate the sheet substrate. In step S02, it is preferable to uniformly diffuse the metal ions contained in the first raw material solution together with the solvent over the entire sheet substrate.
[0020] (Step S03: Impregnation with second raw material solution) In step S03, the sheet substrate impregnated with the first raw material solution in step S02 is impregnated with the second raw material solution prepared in step S01 before the first raw material solution dries. This allows the reaction between the solute of the first raw material solution and the solute of the second raw material solution to proceed smoothly even when the solute of the first raw material solution is difficult to dissolve in the solute of the second raw material solution. Furthermore, even when the solute of the first raw material solution dissolves in the solute of the second raw material solution, the reaction between the solute of the first raw material solution and the solute of the second raw material solution can proceed uniformly. The state in which the first raw solution on the sheet substrate is not dried means that the solvent of the first raw solution remains on the sheet substrate, and more specifically, means that 50% or more of the solvent of the first raw solution remains on the sheet substrate compared to before impregnation. The method of impregnating the sheet substrate with the second raw material solution in step S03 is not limited to a specific method. For example, one or more methods selected from the group consisting of dripping with a dropper, spraying, spray coating, die coating, curtain coating, and dip coating can be used to impregnate the sheet substrate with a sufficient amount of the second raw material solution. Among these, from the viewpoint of preventing contamination of the first raw material solution, it is preferable to use one or more methods selected from the group consisting of dripping with a dropper, spraying, spray coating, die coating, and curtain coating. It is preferable that the amount of the second raw material solution corresponds to the amount of the first raw material solution impregnated in step S02. In step S03, the time for impregnating the sheet substrate with the second raw material solution is preferably 0.01 minutes or more, more preferably 0.05 minutes or more, and even more preferably 0.1 minutes or more, from the viewpoint of penetrating the raw material solution to the center of the substrate. From the viewpoint of ensuring productivity, the time for impregnating the sheet substrate with the second raw material solution is preferably 30 minutes or less, more preferably 15 minutes or less, and even more preferably 5 minutes or less. In step S03, it is preferable to uniformly diffuse the organic ligand contained in the second raw material solution together with the solvent over the entire sheet substrate. This organic ligand reacts with the metal ions that have previously diffused into the sheet substrate in step S02 to produce MOF.
[0021] As an example of step S03, when the MOF is ELM-11, Cu(BF 4 ) 2and the bpy contained in the second raw material solution undergo the following reaction to produce ELM-11. Cu(BF 4 ) 2 +2bpy → Cu(bpy) 2 (B.F. 4 ) 2
[0022] In a typical composite sheet manufacturing process, MOFs are generated in advance and supported on the sheet substrate. Therefore, each MOF particle cannot penetrate into the interior of the sheet substrate by weaving through the gaps between the fibers that make up the substrate, and tends to remain in the surface layer near the surface of the substrate. In other words, in a typical composite sheet manufacturing process, MOFs tend to be concentrated in the surface layer of the substrate. Conversely, if the substrate is configured in such a way that MOFs can penetrate into the substrate, they will quickly fall off, making it difficult to increase the amount of MOFs supported. In contrast, in the manufacturing process of the composite sheet according to the present embodiment, typically, the raw materials before the MOF generation, i.e., metal ions and organic ligands, are diffused into the sheet substrate at the molecular level. By subsequently generating MOF particles, it is possible to support a large amount of MOF not only in the surface layer portion of the sheet substrate but also in the center portion in the thickness direction. The "central portion in the thickness direction" refers to the central portion when the thickness direction is divided equally into three regions. In the manufacturing process of the composite sheet according to the present embodiment, the above-mentioned advantages can be obtained even when the sheet substrate is thick, so that a larger amount of MOF can be supported by using a thicker sheet substrate. From this viewpoint, in the present embodiment, the thickness of the composite sheet is preferably 0.2 mm or more, more preferably 0.5 mm or more, and even more preferably 1 mm or more. The thickness of the composite sheet is practically 10 mm or less, and preferably 5 mm or less. The thickness of the composite sheet complies with JIS K 6402 and the load is 3.7gf / cm 2 The area of the pressure surface of the gauge head is 10 cm 2 The average value is calculated from measurements taken at five locations in total, four corners and one center location, when viewed in a plane.
[0023] In the above-mentioned general composite sheet manufacturing process, in the process of spraying or applying MOFs to the sheet substrate, few MOF particles reach the area on the sprayed or applied surface opposite the fiber, making it difficult to uniformly support MOFs over the entire surface of the fiber. In contrast, in the manufacturing process of the composite sheet according to the present embodiment, the metal ions and organic ligands can be diffused thoroughly throughout the three-dimensional structure of the sheet substrate together with the solvent, and therefore the MOF can be supported uniformly over the entire surface of the fibers constituting the sheet substrate.
[0024] As a comparative example of the present embodiment, a manufacturing process using a method of drying the sheet substrate impregnated with the first raw material solution before step S03 will be described. In the manufacturing process of the composite sheet according to the comparative example, in the process of drying the sheet substrate before step S03, the solvent is evaporated and removed from the surface side of the sheet substrate. Therefore, the solvent in the center of the thickness direction of the sheet substrate diffuses to the surface side together with the metal ions and solidifies. As a result, in the manufacturing process of the composite sheet according to the comparative example, the solute of the first raw material solution is unevenly distributed in the surface layer part of the sheet substrate before the second raw material solution is impregnated. Therefore, the amount of MOF that can be generated in the center of the thickness direction of the sheet substrate is reduced. Also, in the manufacturing process of the composite sheet according to the comparative example, the solute of the first raw material solution is generated as a solid in the sheet substrate before the second raw material solution is impregnated. Therefore, even if the second raw material solution is impregnated, it is difficult for the solute of the first raw material solution to dissolve in the solvent of the second raw material solution and become a metal ion. As a result, the metal ions tend to remain as unreacted substances without reacting with the organic ligands.
[0025] In the manufacturing process of the composite sheet according to this embodiment, it is preferable to impregnate the sheet substrate impregnated with the first raw solution in step S02 with the second raw solution in the presence of the solvent of the first raw solution in step S03 without drying the sheet substrate impregnated with the first raw solution. This makes it possible to solve the above-mentioned problems that occur in the manufacturing process of the composite sheet according to the comparative configuration example. That is, in the manufacturing process of the composite sheet according to this embodiment, the metal ions contained in the first raw material solution can react with the organic ligands contained in the second raw material solution in a state where they are uniformly dispersed in the sheet base material. In addition, in the manufacturing process of the composite sheet according to the present embodiment, the reaction proceeds by efficiently bonding the metal ions and organic ligands that are present in the solvent without being bound by any binding force, so that the metal ions and organic ligands are unlikely to remain as unreacted substances. Therefore, in the manufacturing process for the composite sheet according to this embodiment, it is possible to support more MOFs on the sheet substrate than in the manufacturing process for the composite sheet according to the comparative configuration example.
[0026] In the manufacturing process of the composite sheet according to this embodiment, it is considered that the reaction between the metal ions and the organic ligands proceeds with heterogeneous nucleation at the interface of the fibers constituting the sheet substrate. Intermolecular forces act between the MOFs generated in this manner with heterogeneous nucleation and the interface of the fibers. Therefore, the MOFs generated in step S03 are directly supported on the interface of the fibers by this intermolecular force without the intervention of other components. Therefore, in the manufacturing process of the composite sheet according to this embodiment, it is not necessary to use a binder as an adhesive component to support the MOFs on the surface of the fibers. In this specification, "MOF is directly supported on the fiber surface" means that MOF is fixed to the fiber surface without any other components other than MOF and fiber material. Typically, MOF is fixed by intermolecular forces as described above, by hydrophobic interactions as described below, or by melting and fixing the resin on the fiber surface to the MOF. As a result, in the composite sheet according to this embodiment, the performance degradation caused by the presence of the binder, such as the deterioration of the gas adsorption performance of the MOF due to the adhesion of the binder and the deterioration of the flexibility due to the binder, is unlikely to occur. For this reason, in the composite sheet of the present invention, it is preferable that the MOF is directly supported on the surface of the fiber. Such an effect is mainly obtained by the generation of the MOF by the reaction between the metal ion and the organic ligand as described above, and is not limited to only the configuration exemplified in the examples described later, but can also be effectively obtained with other configurations.
[0027] In the composite sheet according to the present embodiment, the interfiber distance, defined as the dimension of the gap between the fibers constituting the sheet substrate, is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 50 μm or more, and even more preferably 100 μm or more. This ensures the structural flexibility of the MOFs supported on the fiber surfaces, and suppresses the MOFs from falling off. In other words, it is easy to obtain high flexibility of the composite sheet, and the space for the MOFs to be formed is secured, thereby increasing the support rate. The distance between fibers is preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 400 μm or less, and even more preferably 300 μm or less. This suppresses homogeneous nucleation during the reaction between metal ions and organic ligands, and more effectively generates heterogeneous nucleation. In other words, the formation site of MOF can be controlled to be the surface of the fiber. A method for measuring the interfiber distance of the sheet substrate in the composite sheet according to this embodiment will be described. First, an arbitrary surface of the composite sheet to be measured is observed by SEM to obtain an enlarged image of the surface. In the enlarged image, 50 voids formed by each fiber are selected, and the total area of the voids is measured and divided by the number of voids, 50, to obtain the average void area per void. From the average void area per void obtained here, the average interfiber diameter when the voids are converted into a circle is calculated using the following formula, and this average interfiber diameter is taken as the interfiber distance. Average interfiber diameter = 2 x (average void area / 3.14)^(1 / 2) In the composite sheet according to the present embodiment, the basis weight of the sheet substrate is preferably 10 g / m 2More preferably, 20 g / m 2 More preferably, it is 100 g / m 2 Less than 80 g / m 2 In addition, when the sheet base material is laminated and used as one sheet base material, the total basis weight of the sheet base material is 100 g / m or less. 2 A configuration exceeding this is preferred.
[0028] (Step S04: Drying) In step S04, the sheet substrate on which the MOFs are supported in step S03 is dried. In step S04, the solvent is evaporated and removed from the surface layer side of the sheet substrate during the drying process, and the solvent in the center of the thickness direction of the sheet substrate diffuses to the surface layer side. However, the MOFs already fixed to the surface of the fibers in the center of the thickness direction of the sheet substrate remain on the surface of the fibers without moving with the solvent. Therefore, in the manufacturing method of the composite sheet according to this embodiment, the dispersed state of the MOFs supported on the sheet substrate in step S04 is maintained.
[0029] In the method for producing a composite sheet according to the present invention, the series of steps S02 to S04 may be carried out a total of once, that is, they do not necessarily have to be carried out repeatedly. On the other hand, the amount of MOF supported on the sheet substrate can be increased by repeating steps S02 to S04. From this viewpoint, the total number of steps S02 to S04 is preferably two or more, and more preferably three or more. Since there is a limit to the amount of MOF that can be supported on the sheet substrate, in the manufacturing method of the composite sheet according to this embodiment, from the viewpoint of manufacturing costs, etc., it is preferable to limit the total number of steps S02 to S04 to 20 times or less, more preferably 15 times or less, and even more preferably 10 times or less.
[0030] (Step S05: Heat treatment) In step S05, the sheet substrate dried in step S04 is subjected to a heat treatment. The heat treatment in step S05 can be performed by, for example, holding the sheet substrate at 140° C. for 2 hours. The MOF generated in step S03 is in a hydrated state and does not have gas adsorption function. In step S05, it is preferable that the solvent component remaining on the sheet substrate is completely removed. In step S05, the MOF is dehydrated to allow the gas adsorption function of the MOF to be expressed, thereby obtaining the composite sheet according to the present embodiment.
[0031] [Another example of the manufacturing method of the composite sheet] The method for producing a composite sheet according to the present embodiment is not limited to the above basic configuration. For example, in the method for producing a composite sheet according to the present embodiment, it is preferable that, in step S01, one of metal ions and organic ligands, which are raw materials for MOF, is contained in the first raw material solution, and the other is contained in the second raw material solution. In step S01, it is preferable that the first raw material solution contains metal ions and the second raw material solution contains organic ligands as described above. In addition to this configuration, the first raw material solution may contain an organic ligand, and the second raw material solution may contain a metal ion.
[0032] In the manufacturing method of the composite sheet according to the present embodiment, in step S01, it is preferable that one of the first raw solution and the second raw solution contains water as a solvent and the other contains an organic solvent as a solvent. In step S01, as described above, it is preferable that the first raw material solution contains water as a solvent, and the second raw material solution contains an organic solvent as a solvent. In addition to this configuration, the first raw material solution may contain an organic solvent as a solvent, and the second raw material solution may contain water as a solvent. In step S01, the organic solvent used may be other than ethanol, and may include, for example, methanol, isopropanol, acetone, or the like. The organic solvent is preferably one which is miscible with water in any ratio.
[0033] In the method for producing a composite sheet according to the present embodiment, in step S01, the water content in the first raw solution or the second raw solution that contains water as a solvent is preferably 30% by mass or more and 99% by mass or less. In addition, in the method for producing a composite sheet according to the present embodiment, in step S01, the organic solvent content in the first raw solution or the second raw solution that contains an organic solvent as a solvent is preferably 30% by mass or more and 99% by mass or less. By setting the values in these ranges, the raw solution can easily permeate into the sheet base material, and the MOF can easily be fixed uniformly in the thickness direction of the composite sheet.
[0034] The method for producing a composite sheet according to the present embodiment may include additional steps in addition to the steps described above, if necessary. Also, in the method for producing a composite sheet according to the present embodiment, some of the steps described above may be modified or omitted, if necessary. For example, the drying time in step S04 can be shortened by heating to a temperature higher than room temperature and lower than the heat treatment temperature in step S05. In this case, the drying in step S04 and the heat treatment in step S05 can be performed in a single heating process.
[0035] In the method for producing a composite sheet according to the present embodiment, it is preferable to use a sheet substrate at least partially composed of organic fibers, which allows the MOF to be more firmly fixed to the surface of the organic fibers by hydrophobic molecular interactions between the organic ligands of the MOF and the groups present on the surface of the organic fibers. Such hydrophobic interactions are observed not only in hydrophobic organic fibers but also in hydrophilic organic fibers. In other words, even if an organic fiber is hydrophilic as a whole, compositional interactions will occur if there are hydrophobic parts at the micro level. For example, in cellulose fibers, which are hydrophilic organic fibers, the CH groups constituting the axial groups of the glucopyranose rings are hydrophobic, so hydrophobic interactions will occur. Whether the fibers constituting the sheet substrate in a composite sheet are hydrophilic or hydrophobic is determined based on the actual surface properties of the fibers, regardless of the inherent properties of the fibers themselves. In other words, for surface-treated fibers, the determination is based on the state after surface treatment. For example, a hydrophobic fiber whose surface has been hydrophilically treated is a hydrophilic fiber, and a hydrophilic fiber whose surface has been hydrophobically treated is a hydrophobic fiber. To evaluate whether the fibers constituting the sheet substrate in the composite sheet are hydrophilic or hydrophobic, deionized water is sprayed onto the composite sheet, and the contact surface between each fiber and the deionized water is observed using a microscope, etc. If the contact angle between the fiber and the deionized water is less than 60°, the surface of the fiber is judged to be hydrophilic, and if the contact angle is 60° or more, the surface of the fiber is judged to be hydrophobic.
[0036] In the method for producing a composite sheet according to the present embodiment, it is preferable to use a sheet substrate containing both hydrophilic and hydrophobic fibers, which increases the permeation rate of either water or an organic solvent into the sheet substrate impregnated with the other in step S03, making it difficult for MOFs to be unevenly distributed in the sheet substrate.
[0037] The sheet substrate according to this embodiment preferably contains, as hydrophilic organic fibers, one or more selected from cellulose fibers, regenerated cellulose fibers, thermoplastic fibers with hydrophilized surfaces, and the like. More preferably, the regenerated cellulose fibers contain one or more selected from rayon, cupra, and the like. Methods for making the surface of thermoplastic fibers hydrophilic include, for example, coating with a hydrophilizing agent and carrying out a plasma treatment. The thermoplastic fibers preferably contain one or more resins selected from polyolefin resin, polyester resin, vinyl resin, acrylic resin, fluororesin, polyamide resin, and the like. The polyolefin resin preferably contains one or more selected from polyethylene, polypropylene, and the like. The polyester resin preferably contains one or more resins selected from polyethylene terephthalate and the like. The vinyl resin preferably contains one or more resins selected from polyvinyl chloride, polystyrene, and the like. The acrylic resin preferably contains one or more resins selected from polyacrylic acid, polymethyl methacrylate, and the like. The fluororesin preferably contains one or more resins selected from polyperfluoroethylene and the like. Moreover, the sheet substrate according to the present embodiment preferably contains one or more hydrophobic organic fibers selected from synthetic fibers and the like. The synthetic fibers preferably include one or more selected from polyolefin fibers, polyester fibers, fluorine fibers, polyamide fibers, and the like. In the present embodiment, a part or all of the fibers constituting the sheet substrate may be inorganic fibers. The sheet substrate according to the present embodiment preferably contains, as the inorganic fibers, one or more selected from, for example, glass fibers, ceramic fibers, metal fibers, carbon fibers, and the like.
[0038] In the method for producing a composite sheet according to the present embodiment, the organic fiber constituting the sheet substrate may be a core-sheath fiber, which is a composite fiber in which the resin constituting the core is different from the resin constituting the sheath that covers the core and constitutes the surface of the fiber. In the core-sheath fiber used in this embodiment, the melting point of the core is preferably higher than that of the sheath, and more preferably is 20° C. or more higher than that of the sheath. In the sheath-core fiber used in this embodiment, the melting point of the core is preferably 160° C. or higher, and the melting point of the sheath is preferably 80° C. or higher. Furthermore, in the sheath-core fiber, the melting point of the core is preferably higher than the heat treatment temperature in step S05. Furthermore, in the sheath-core fiber, the melting point of the sheath is preferably higher than the drying temperature in step S04 and lower than the heat treatment temperature in step S05. By setting the melting point of the sheath part of the core-sheath fiber higher than the drying temperature in step S04, it is possible to prevent the sheath part from melting in step S04 and taking in the reactants into the fiber. Therefore, the MOF production reaction can be steadily promoted and the reactivity of the MOF production reaction can be increased. In addition, by setting the melting point of the sheath part of the core-sheath fiber lower than the heat treatment temperature in step S05, the MOF can be more reliably fixed to the surface of the fiber. Furthermore, by setting the melting point of the core part of the core-sheath fiber higher than the heat treatment temperature in step S05, the fiber shape is maintained by the core part that does not melt in step S05. Therefore, the gaps between the fibers of the sheet substrate are maintained, and the reactivity of the MOF production reaction can be increased. That is, with this configuration, in the manufacturing method of the composite sheet according to the present embodiment, the core part with a high melting point maintains the fiber shape in the heat treatment in step S05. Also, the resin in the sheath part with a low melting point melts and adheres to the MOF, thereby fixing the MOF. As a result, in the manufacturing method of the composite sheet according to the present embodiment, the MOF can be fixed more firmly to the surface of the fiber made up of the sheath part. In this embodiment, the fibers constituting the sheet substrate preferably include, for example, core-sheath fibers in which the core portion is made of polyethylene terephthalate and the sheath portion is made of polyethylene.
[0039] [Composite Sheet Detail Configuration] (Surface coverage) In the composite sheet according to this embodiment, it is possible to support MOFs throughout the entire three-dimensional structure of the sheet substrate made of fibers in step S03. That is, in the composite sheet according to this embodiment, a large number of MOFs can be supported not only in the surface layer portion of the sheet substrate but also in the center portion in the thickness direction. Specifically, in the composite sheet according to this embodiment, in the center portion in the thickness direction of the composite sheet, the surface coverage rate, which is defined as the ratio of the area covered by MOFs to the surface of the fibers, is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and practically 100% or less.
[0040] The surface coverage of the fibers constituting the sheet base material of the composite sheet by MOFs can be determined using SEM and energy dispersive X-ray spectroscopy (EDX). Specifically, the composite sheet is cut, and the unsupported MOFs are removed by a blower or the like. Then, a microstructure photograph is taken of the entire cut surface by SEM. In the obtained microstructure photograph, a perpendicular line is drawn to a straight line along the width direction of the composite sheet, and a midpoint between both ends of the composite sheet in the thickness direction on the perpendicular line is determined. The part on the straight line along the width direction passing through the midpoint is defined as the center of the composite sheet in the thickness direction. Then, focusing on any one fiber present in the center of the thickness direction of the composite sheet, a microstructure photograph is taken of the one fiber by SEM, and an element mapping image is generated by EDX. As a result, the area where the fibers exist can be identified by the microstructure photograph, and the area where the metal exists can be identified as the area where the MOF exists by the element mapping image. Then, the surface coverage can be calculated as the ratio of the area where the MOF exists to the entire area where the fibers exist.
[0041] (Circumferential coverage) In the composite sheet according to the present embodiment, it is possible to uniformly support MOFs over the entire circumference of the surface of the fibers constituting the sheet substrate. As a result, in the composite sheet according to the present embodiment, it is possible to increase the circumferential coverage, which is defined as the ratio of the area covered by MOFs to the surface of the fibers observed as the outline of the fibers in a cross section perpendicular to the longitudinal direction of the fibers constituting the sheet substrate. Specifically, in the composite sheet according to the present embodiment, the circumferential coverage by MOFs in at least a part of the fibers constituting the sheet substrate is preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, and practically 100% or less. More preferably, the circumferential coverage by MOFs in at least a part of the fibers constituting the middle region when the cross section of the composite sheet is equally divided into three regions in the thickness direction is 80% or more. The shape of the outline of the fibers is not particularly limited, and may be any shape such as a circle, a square, a triangle, or a star. In any case, the circumferential coverage can be calculated by determining the length of the entire circumference of the surface of the fibers by a known method.
[0042] The circumferential coverage of the surface of the fiber constituting the sheet substrate of the composite sheet by the MOF can be determined using SEM and EDX. Specifically, a microstructure photograph is taken by SEM in a field of view in which a cross section perpendicular to the longitudinal direction of the fiber in the cross section of the composite sheet can be observed, and an element mapping image is generated by EDX. Then, the length of the entire area of the fiber surface observed as the outline of the fiber in the cross section perpendicular to the longitudinal direction of the fiber and the length of the area covered by the MOF on the fiber surface observed as the outline of the fiber are measured, and the circumferential coverage can be calculated as the ratio of these using the following formula. Circumferential coverage by MOF (%) = 100 × (length of the area of the fiber surface covered by MOF / length of the entire area of the fiber surface)
[0043] (Thickness of the MOF layer covering the fiber) Whether or not the fiber surface is covered with MOF and the thickness of the MOF layer covering it are measured as follows. A two-part curing liquid epoxy resin and a hardener are mixed and impregnated into the sheet to be measured. The mixture is then degassed in a vacuum and then heat-treated to harden the epoxy resin and hardener. This results in a hardened sample in which the positions of the fiber and MOF are fixed. The obtained cured sample is cut along the thickness direction of the sheet, and its surface is observed by SEM. The cross-sectional portion of the fiber coated with MOF is extracted from the cross-sectional image of the obtained composite sheet. The average thickness of the MOF layer in the radial direction of the fiber in the portion coating the fiber is taken as the thickness of the MOF layer.
[0044] (MOF content ratio) In the composite sheet according to the present embodiment, by increasing the surface coverage and circumferential coverage of the fibers constituting the sheet substrate by the MOF as described above, it is possible to support more MOFs on the sheet substrate, i.e., to increase the content of MOFs. Specifically, in the composite sheet according to the present embodiment, the content of MOFs, defined as the ratio of the mass of MOFs to the mass of the entire composite sheet after heat treatment, is preferably 80% by mass or more, more preferably 85% by mass or more. In addition, in the composite sheet according to the present embodiment, the content of MOFs is preferably 99% by mass or less.
[0045] The content ratio of MOF in the composite sheet can be determined by analyzing the composite sheet. Specifically, gas adsorption measurement, X-ray diffraction (XRD), EDX, nuclear magnetic resonance (NMR), infrared spectroscopy (IR), elemental analysis, etc. are first performed to determine the pore structure, crystal lattice size, crystal structure, and constituent elements. The type of MOF, i.e., metal ions and organic ligands, is identified by comparing these results with a publicly available MOF database. Then, the composite sheet is pyrolyzed and the amount of metal contained in the remaining ash is measured. Next, the mass of MOF contained in the composite sheet is determined from the measured amount of metal and the metal content of the identified MOF. The content ratio of MOF is then obtained by dividing the determined mass of MOF by the mass of the composite sheet.
[0046] (MOF surface exposure rate) In the composite sheet according to this embodiment, it is not necessary to mainly rely on a binder as an adhesive component. Therefore, in the composite sheet according to this embodiment, the binder does not cover the surface of the MOF, and the surface exposure rate can be increased. The surface exposure rate is defined as the ratio of the area of the area where the surface of the MOF is exposed to the area of the area occupied by the MOF supported on the fiber constituting the sheet substrate when the composite sheet is viewed in plan (100 x (area of the area where the surface of the MOF is exposed) / (area of the area occupied by the MOF supported on the sheath part of the core-sheath fiber constituting the sheet substrate)). Specifically, in the composite sheet according to this embodiment, the surface exposure rate of the MOF is preferably 50% or more and 100% or less, more preferably 70% or more, and even more preferably 90% or more.
[0047] The surface exposure rate of the MOF in the composite sheet is measured by first removing the MOF that is not supported on the fiber constituting the sheet substrate in the composite sheet with a blower or the like. Then, the surface of the MOF supported on the fiber constituting the sheet substrate can be evaluated by surface analysis and mapping using time-of-flight secondary ion mass spectrometry (TOF-SIMS), microscopic IR, or the like. Specifically, the site where the MOF is observed is identified, and its area (area of the area occupied by the MOF) is measured and the MOF surface is analyzed. By analyzing the MOF surface, the area of the area on the MOF where the spectrum originating from a substance other than the MOF is detected is measured. The substance other than the MOF is, for example, derived from the binder, etc. Then, the area of the area where the spectrum originating from a substance other than the MOF is detected is subtracted from the area occupied by the MOF. The surface exposure rate of the MOF can be calculated by dividing the difference area by the surface area of the MOF.
[0048] (Gas adsorption amount per unit volume of composite sheet) Similarly, in the composite sheet according to this embodiment, the surface of the MOF is not covered by the adhesion of the binder. Therefore, the surface exposure rate of the MOF is high. In addition, in the composite sheet according to this embodiment, as explained in the above section "Step S03: Impregnation with the second raw material solution" by comparison with the comparative configuration example, there is little unreacted material of the MOF. Therefore, the gas adsorption performance is less likely to be hindered. As a result, in the composite sheet according to this embodiment, the MOF supported on the sheet base material can effectively exhibit its original gas adsorption performance. In addition, the MOF can be fixed to the fibers in the center of the composite sheet, and the composite sheet also has high air permeability. Therefore, in the composite sheet according to this embodiment, the gas adsorption amount per unit volume of the composite sheet can be increased. Specifically, in the composite sheet according to this embodiment, when ELM-11 is used as the MOF that selectively adsorbs carbon dioxide, the gas adsorption amount per unit volume of the composite sheet is preferably 2 mL / cm. 3 More preferably, 3 mL / cm 3 More preferably, 5 mL / cm3 That's all. In addition, for example, when ZIF-8 is used as the MOF for adsorbing carbon dioxide, the gas adsorption amount per unit volume of the composite sheet is preferably 0.5 mL / cm. 3 More preferably, 0.7 mL / cm 3 More preferably, 1.0 mL / cm 3 That's all.
[0049] The gas adsorption amount per unit volume of the composite sheet is obtained by dividing the gas adsorption amount measured for the composite sheet by the volume of the composite sheet measured. The gas adsorption amount is measured using a high-precision gas adsorption amount measuring device "BELSORP-miniII" manufactured by MicrotrackBell.
[0050] (MOF dropout rate) In the composite sheet according to this embodiment, the MOFs can be firmly fixed to the fiber surfaces without relying primarily on a binder as an adhesive component for fixing the MOFs to the fiber surfaces. In the composite sheet of this embodiment, the MOF dropout rate in a shaking evaluation in which the composite sheet is grasped with the hand and shaken up and down is preferably 0 mass% or more and 20 mass% or less, more preferably 18 mass% or less, even more preferably 15 mass% or less, and even more preferably 9 mass% or less. As a result, in the composite sheet according to the present embodiment, the amount of MOFs supported on the sheet substrate is easily maintained during transportation and use, so that the gas adsorption performance is less likely to decrease. In addition, in the composite sheet according to the present embodiment, it is possible to prevent the MOFs that fall off during use from being mixed into the equipment as foreign matter. The MOF detachment rate was obtained by dividing the mass of the MOF detached during the shaking evaluation by the mass of the MOF contained in the composite sheet before the shaking evaluation.
[0051] (Maximum bending stress of composite sheet) The composite sheet according to the present embodiment is easily flexible because it does not rely mainly on a binder as an adhesive component for fixing the MOFs to the fiber surface, which allows the composite sheet according to the present embodiment to be highly processable and to be stored and transported in a rolled form. In the composite sheet according to this embodiment, the maximum bending stress is preferably 0 MPa or more and 5 MPa or less, more preferably 3 MPa or less, even more preferably 1 MPa or less, and even more preferably 0.1 MPa or less.
[0052] The maximum bending stress of the composite sheet can be measured using a measuring device (Shimadzu Corporation's universal testing machine AG-X plus) in accordance with the three-point bending test of JIS K7017. At this time, the composite sheet to be measured is cut into a sample measuring 100 mm long x 100 mm wide and measured. In the three-point bending evaluation, the sample is placed on a jig with a support distance of 40 mm, and the center part between the supports is pressed at a speed of 10 mm / min to measure the pressing amount and bending load. The maximum value of the bending stress obtained from this evaluation is taken as the maximum bending stress. The bending stress is a physical property calculated by dividing the moment (the product of the load and distance) applied to the sample during the three-point bending test by the section modulus of the sample, and is calculated using the following formula. Bending stress (MPa) = 3 × bending load (N) × support distance (m) / 2 / sample thickness (m) / (sample width (m) 2 ) / 10 6 When the size of the composite sheet to be measured makes it impossible to cut out the sample, a sample having any size may be cut out and measured.
[0053] (Gurley air permeability of composite sheet) The composite sheet according to the present embodiment is preferably configured to allow gas to pass through with low pressure loss so that gas can be easily supplied to the MOF supported at the center in the thickness direction of the composite sheet. Specifically, the composite sheet according to the present embodiment has a Gurley air permeability of preferably 0 sec / 100 mL or more and 10 sec / 100 mL or less, more preferably 5 sec / 100 mL or less, and even more preferably 0.5 sec / 100 mL or less. The Gurley air permeability of the composite sheet can be determined using a Gurley air permeability tester in accordance with JIS P8117:2009.
[0054] (Identifying the type of fiber that makes up the sheet base material) The type of fiber constituting the sheet substrate in the composite sheet can be identified using TOF-SIMS, IR, NMR, EDX, differential scanning calorimetry (DSC), etc. Specifically, the type of fiber can be identified by identifying the structural formula of the fiber constituting the sheet substrate in the composite sheet using TOF-SIMS, IR, NMR, EDX, etc., and measuring the melting point by DSC.
[0055] [Other embodiments] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and it goes without saying that various modifications can be made without departing from the spirit of the present invention.
[0056] For example, in the method for producing a composite sheet according to the present embodiment, from the viewpoint of the permeation speed of the first and second raw solution into the sheet substrate, it is preferable that one of the solvents used in the first and second raw solution prepared in step S01 contains water and the other contains an organic solvent, but from another viewpoint, a different configuration may be adopted. For example, in the method for producing a composite sheet according to the present embodiment, both of the solvents used in the first and second raw solution prepared in step S01 may contain water or an organic solvent.
[0057] The composite sheet according to the present embodiment preferably does not contain a binder, but may contain a small amount of binder when it is necessary to fix the MOF more firmly to the sheet base material, etc. However, in the composite sheet according to the present embodiment, from the viewpoint of ensuring high gas adsorption performance of the MOF and high flexibility, it is preferable that the ratio of the mass of the binder to the total mass of the MOF and the binder is kept to 0 mass% or more and 5 mass% or less. In the composite sheet according to this embodiment, the content of the binder relative to the mass of the entire composite sheet is 0 mass % or more and 10 mass % or less, preferably 5 mass % or less, and more preferably 1 mass % or less.
[0058] The present invention further includes the following configurations. <1> A composite sheet in which a metal organic framework is dispersed in a sheet base material composed of fibers, The metal-organic framework is supported on the surface of the fiber, The ratio of the mass of the metal organic framework to the mass of the entire composite sheet is 80 mass% or more; a surface coverage rate of the fibers constituting a central portion of the composite sheet in a thickness direction by the metal-organic framework is 60% or more and 100% or less; The surface exposure rate of the metal organic framework is 50% or more. Composite sheet. <2> In at least a part of the fiber, a circumferential coverage rate by the metal-organic framework in a cross section perpendicular to the longitudinal direction is 80% or more and 100% or less, preferably 85% or more, and more preferably 90% or more. <1> The composite sheet according to claim 1. <3> The dropout rate of the metal-organic framework as determined by shaking is 0% by mass or more and 20% by mass or less, preferably 18% by mass or less, more preferably 15% by mass or less, and further preferably 9% by mass or less. <1> or <2> The composite sheet according to claim 1. <4> The maximum bending stress is 0 MPa or more and 5 MPa or less, preferably 3 MPa or less, more preferably 1 MPa or less, and further preferably 0.1 MPa or less. <1> from <3> 13. The composite sheet according to claim 12 . <5> The fibers include organic fibers. <1> from <4> 13. The composite sheet according to claim 12 . <6> The fibers include hydrophilic fibers and hydrophobic fibers. <1> from <5> 13. The composite sheet according to claim 12 . <7> The hydrophilic fibers include cellulosic fibers and the hydrophobic fibers include synthetic fibers. <6> The composite sheet according to claim 1. <8> The surface exposure rate of the metal-organic framework is 50% or more and 100% or less, preferably 70% or more, and more preferably 90% or more. <1> from <7> 13. The composite sheet according to claim 12 . <9> The binder is 0% by mass or more and 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, based on the total mass of the metal organic framework. <1> from <8> 13. The composite sheet according to claim 12 . <10> The composite sheet contains a binder in an amount of 0% by mass or more and 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, based on the total mass of the composite sheet. <1> from <9> 13. The composite sheet according to claim 12 . <11> The composite sheet does not include a binder. <1> from <9> 13. The composite sheet according to claim 12 . <12> The metal-organic framework is supported directly on the surface of the fiber. <1> from <11> 13. The composite sheet according to claim 12 . <13> A layer of the metal-organic framework is formed on the surface of the fiber. <1> from <12> 13. The composite sheet according to claim 12 . <14> The surface coverage rate of the fibers constituting the central portion in the thickness direction of the composite sheet by the metal-organic framework is 70% or more, and preferably 80% or more. <1> from <13> 13. The composite sheet according to claim 12 . <15> The metal-organic framework is configured to be capable of selectively adsorbing carbon dioxide. <1> from <14> 13. The composite sheet according to claim 12 . <16> The thickness of the composite sheet is 0.2 mm or more and 10 mm or less, preferably 0.5 mm or more and 5 mm or less, and more preferably 1 mm or more. <1> from <15> 13. The composite sheet according to claim 12 . <17> The Gurley air permeability of the composite sheet is 0 sec / 100 mL or more and 10 sec / 100 mL or less, preferably 5 sec / 100 mL or less, and more preferably 0.5 sec / 100 mL or less. <1> from <16> 13. The composite sheet according to claim 12 . <18> The sheet substrate is a nonwoven fabric. <1> from <17> 13. The composite sheet according to claim 12 . <19> The content ratio of the metal organic framework is 80 mass % or more and 99 mass % or less, preferably 85 mass % or more, based on the total mass of the composite sheet. <1> from <18> 13. The composite sheet according to claim 12 . <20> The fiber maintains its fibrous form. <1> from <19> 13. The composite sheet according to claim 12 . <21> The interfiber distance of the sheet substrate in the composite sheet is 1 μm or more and 1000 μm or less, preferably 10 μm or more and 500 μm or less, more preferably 50 μm or more and 400 μm or less, and further preferably 100 μm or more and 300 μm or less. <1> from <20> 13. The composite sheet according to claim 12 . <22> A method for producing a composite sheet in which a metal organic framework is supported on a sheet base material composed of fibers, comprising the steps of: A first raw material solution containing one of metal ions and organic ligands that are raw materials for the metal organic framework, and a second raw material solution containing the other are prepared; impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; drying the sheet base material impregnated with the second raw material solution; The sheet substrate impregnated with the second raw material solution is subjected to a heat treatment; Before the heat treatment, the ratio of the mass of the metal organic framework to the mass of the entire composite sheet after the heat treatment is 80 mass% or more. impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; The sheet substrate impregnated with the second raw material solution is dried. Repeat the process A method for manufacturing a composite sheet. <23> One of the first raw solution and the second raw solution contains 30% by mass or more and 99% by mass or less of water, and the other contains 30% by mass or more and 99% by mass or less of an organic solvent. <22> A method for producing the composite sheet according to claim 1. <24> The fibers include organic fibers. <22> or <23> A method for producing the composite sheet according to claim 1. <25> The fibers include hydrophilic fibers and hydrophobic fibers. <22> from <24> 13. A method for producing the composite sheet according to claim 12. <26> The first raw material solution contains the metal ions, and the second raw material solution contains the organic ligands. <22> from <25> 13. A method for producing the composite sheet according to claim 12. <27> The solvent of the first raw material solution contains water, and the solvent of the second raw material solution contains an organic solvent. <26> A method for producing the composite sheet according to claim 1. <28> Before the heat treatment, impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; The sheet substrate impregnated with the second raw material solution is dried. The total number of steps is 2 to 20, preferably 2 to 15, more preferably 3 to 10. <22> from <27> 13. A method for producing the composite sheet according to claim 12. <29> The metal-organic framework is dehydrated by the heat treatment. <22> from <28> 13. A method for producing the composite sheet according to claim 12. <30> the fibers comprise sheath-core fibers, In the core-sheath fiber, the melting point of the core is higher than the temperature of the heat treatment, and the melting point of the sheath is higher than the temperature of the drying and lower than the temperature of the heat treatment. <22> from <29> 13. A method for producing the composite sheet according to claim 12. <31> The time for impregnating the sheet substrate with the first raw material solution is 0.1 minutes or more and 30 minutes or less. <22> from <30> 13. A method for producing the composite sheet according to claim 12. <32> The time for impregnating the sheet substrate with the second raw material solution is 0.1 minutes or more and 30 minutes or less. <22> from <31> 13. A method for producing the composite sheet according to claim 12. <33> At least one of the first raw solution and the second raw solution is impregnated into the sheet substrate by one or more methods selected from the group consisting of dripping with a dropper, misting, spray coating, die coating, and curtain coating. <22> from <32> 13. A method for producing the composite sheet according to claim 12. <34> The concentration of the metal ion in the first raw solution and the concentration of the organic ligand in the second raw solution are both 0.05 mol / L or more and 10 mol / L or less. <26> or <27> A method for producing the composite sheet according to claim 1.
[0059] [Examples and Comparative Examples] (Examples 1 to 10) As an example of the present invention, a composite sheet sample was produced using the above manufacturing method. In Examples 1 to 6 and 8 to 10, an airlaid nonwoven fabric containing hydrophilic and hydrophobic fibers in the mass ratios shown in Table 1 was used as the sheet substrate. Softwood chemical pulp (NBKP), which is a cellulose fiber, was used as the hydrophilic organic fiber. In addition, core-sheath fibers in which the core is made of polyethylene terephthalate (PET) with a melting point of 260°C and the sheath is made of polyethylene (PE) with a melting point of 130°C were used as the hydrophobic organic fiber. In Example 7, a nonwoven fabric made of regenerated cellulose fibers (manufactured by Asahi Kasei Corporation, product name "Benliese", basis weight 40 g / m) was used as the sheet substrate. 2 ) was used. In each of Examples 1 to 7, ELM-11 configured to be capable of selectively adsorbing carbon dioxide was used as the MOF. In each of Examples 8 to 10, ZIF-8 configured to be capable of adsorbing carbon dioxide was used as the MOF. Table 1 shows, for each of Examples 1 to 10, the thickness of the composite sheet, the basis weight of the sheet substrate, the concentrations of the first and second raw solution prepared in step S01, the number of steps S02 to S04, the application amount of the first raw solution in step S02, the application amount of the second raw solution in step S03, the heat treatment temperature in step S05, and the average inter-fiber distance.
[0060] The specific configurations of steps S01 to S05 in each of the embodiments 1 to 10 are as follows. In step S01 in Examples 1 to 7, Cu(BF 4 ) 2 The aqueous solution was diluted with deionized water to prepare a first raw material solution so as to have the concentration shown in Table 1. In addition, bpy was dissolved in ethanol to prepare a second raw material solution so as to have the concentration shown in Table 1. In step S01 in Examples 8 to 10, a first raw material solution was prepared by diluting a 2-methylimidazole aqueous solution with deionized water to 3.46 mol / L, and a second raw material solution was prepared by dissolving a zinc nitrate aqueous solution in deionized water to 0.77 mol / L. In step S02 in Examples 1 to 10, 14 g of the first raw solution was applied to a 100×100 mm sheet substrate using a dropper so as to obtain the application amount shown in Table 1. In all Examples, the time for impregnating the sheet substrate with the first raw solution was about 2 minutes, and the first raw solution was able to sufficiently permeate the sheet substrate. In step S03 in Examples 1 to 10, the second raw solution was applied to the sheet substrate to which the first raw solution was applied in step S02, before the sheet substrate dried, using a dropper in an amount shown in Table 1. In all Examples, the time for impregnating the sheet substrate with the second raw solution was about 2 minutes, and the second raw solution was able to sufficiently permeate the sheet substrate. In step S04 in Examples 1 to 10, the sheet substrate to which the second raw material solution was applied in step S03 was dried overnight in a draft. Steps S02 to S04 were repeated the number of times shown in Table 1. In step S05, the sheet after steps S02 to S04 were repeated the number of times shown in Table 1 was left standing in a drying furnace at the heat treatment temperature shown in Table 1 for 2 hours. In all examples, the fibers in the sheet maintained their morphology, and the MOFs were directly supported on the surface of the fibers, forming a layer of MOFs on the surface of the fibers.
[0061] For the composite sheet samples according to Examples 1 to 10, the MOF content ratio, surface coverage ratio, circumferential coverage ratio, surface exposure ratio, MOF layer thickness, fiber diameter, and gas adsorption amount per unit volume were determined using the above-mentioned analysis method. The surface coverage ratio and circumferential coverage ratio were determined for the fibers constituting the central part in the thickness direction of the composite sheet. The MOF layer thickness and fiber diameter were determined for the fibers carrying MOF in a layered form. More specifically, the MOF content ratio, gas adsorption amount per unit volume, gas adsorption amount per unit weight, and gas adsorption amount per unit weight of MOF were determined as follows.
[0062] MOF content ratio The mass of the obtained composite sheet and the mass of the base sheet alone before MOF was supported were calculated using the following formula. MOF content (%) = 100 × (mass of composite sheet - mass of base sheet alone) / mass of sample
[0063] Gas adsorption amount per unit volume The composite sheet sample was cut to a desired size. A BELSORP-miniII (MicrotrackBell) was used to evaluate the gas adsorption amount. As a pretreatment, a vacuum degassing treatment was performed at 100°C for 12 hours, and then the carbon dioxide adsorption isotherm was measured. The amount of adsorption obtained from this result was taken as the amount of carbon dioxide adsorption, and was divided by the volume of the measured composite sheet sample to calculate the amount of gas adsorption per unit volume.
[0064] Gas adsorption amount per unit weight The composite sheet sample was cut to a desired size. A BELSORP-miniII (MicrotrackBell) was used to evaluate the amount of gas adsorption. As a pretreatment, a vacuum degassing treatment was performed at 100°C for 12 hours, and then the carbon dioxide adsorption isotherm was measured. The amount of adsorption obtained from this result was taken as the amount of carbon dioxide adsorption. This was divided by the weight of the measured composite sheet sample to calculate the amount of gas adsorption per unit volume.
[0065] Gas adsorption per unit weight of MOF The amount of carbon dioxide adsorption, obtained in the same manner as the amount of gas adsorption per unit weight, was divided by the measured mass of MOF contained in the composite sheet to calculate the amount of gas adsorption per unit volume.
[0066] Table 2 shows the analysis results for the composite sheet samples according to Examples 1 to 10. In all samples, the surface coverage was 60% or more, and the circumferential coverage was 80% or more. As a result, a high MOF content of 80% by mass or more was obtained in all samples. In addition, the surface exposure rate of the MOF was 100% in all samples. In addition, the gas adsorption amount per unit volume of the composite sheet, the gas adsorption amount per unit weight, and the gas adsorption amount per unit weight of the MOF all showed high values. Therefore, it was presumed that the decrease in the gas adsorption performance of the MOF due to the support by the sheet substrate was suppressed.
[0067] Next, the composite sheet samples according to Examples 1 to 10 were evaluated for the MOF drop rate, maximum bending stress, MOF uniformity, processability, and Gurley air permeability. For processability, a filling property evaluation and an MOF retention evaluation were performed. More specifically, the MOF uniformity and processability were evaluated as follows.
[0068] Uniformity of MOFs The composite sheet sample was cut along the thickness direction to create a cross-sectional observation surface. Then, microstructure photographs were taken using SEM and element mapping images were generated using EDX. The composite sheet sample was divided into three regions in the thickness direction, and each region was set within the observation and analysis area. The content of metals, which are the main components of MOFs, was quantified from the obtained element mapping images, and the average content of metals, which are the main components of MOFs, in the three divided regions, as well as the evaluation value of their uniformity, were calculated using the following formula. Uniformity evaluation value (%) = 100 × (maximum value of the content of the main metal component of MOF - minimum value of the content of the main metal component of MOF) / average value of the content of the main metal component of MOF in the three divided regions The uniformity evaluation value obtained above was rounded off to the nearest tenth, and the result was used as the evaluation result of the MOF uniformity. In other words, for each composite sheet sample, the smaller the evaluation result number, the higher the MOF uniformity, and the larger the evaluation result number, the lower the MOF uniformity.
[0069] ·Workability The processability was evaluated by evaluating the filling property and the MOF retention property. (1) Filling evaluation The composite sheet was cut to a width of 5 cm and a length of 10 cm, and the cut sample was wrapped around a cylinder with a diameter of 1.5 mm along the outer periphery of the cylinder. The stacking state of the obtained roll was checked, and the state of the gaps in the stacked composite sheet samples was checked. For each composite sheet sample, the maximum value of the gaps was taken as the evaluation result of the packing property. In other words, it can be seen that the smaller the evaluation result value for each composite sheet sample, the higher the packing property of the rolled body obtained. (2) MOF retention evaluation The mass of the composite sheet was measured before and after the filling property evaluation test, and the MOF retention rate was calculated using the following formula. MOF retention rate (%) = 100 × (mass of composite sheet after filling property evaluation test / mass of composite sheet before filling property evaluation test) The retention rate of the MOF was used as the evaluation result of the MOF retention. That is, for each composite sheet sample, the higher the evaluation result value, the better the MOF was retained on the fiber surface when processed into a roll.
[0070] As shown in Table 2, in all of the composite sheet samples according to Examples 1 to 10, the MOF dropout rate was as low as 20% by mass or less, and the maximum bending stress was as low as 3.3 MPa or less. As a result, in terms of processability, the gap in the filling evaluation was less than 2 mm, and the MOF retention evaluation was 94 or more, and good evaluation results were obtained. In addition, the MOF uniformity value in all of the samples was 30% or less, and it was found that the MOF was dispersed with high uniformity throughout the entire sheet substrate. In addition, the Gurley air permeability in all of the samples was as low as 0.2 seconds / 100 mL or less, and it was found that high breathability was obtained. It is believed that the high air permeability in each sample contributes to an increase in the amount of gas adsorbed per unit volume.
[0071] In all of Examples 1 to 7, the MOF was more favorable than the following Comparative Examples 1 to 3, which also used ELM-11 as the MOF. 、 The gas adsorption amount per unit volume, the gas adsorption amount per unit weight, and the gas adsorption amount per unit weight of MOF were all large. In addition, in all of Examples 1 to 7, the maximum bending stress was smaller than in Comparative Examples 1 to 3 described below, and the gaps were smaller in the filling property evaluation for processability. This is considered to be because flexibility is guaranteed due to the absence of a binder. Furthermore, in all of Examples 1 to 7, the numerical value of the uniformity of MOF was smaller than in Comparative Examples 1 to 3 described below, and it was found that MOF was uniformly dispersed. This is considered to be because MOF particles were formed on the sheet substrate, and MOF was uniformly distributed over the entire sheet substrate.
[0072] In all of Examples 1 to 7, the uniformity of the MOF was higher than that in Comparative Example 4 below, which also used ELM-11 as the MOF, and the gas adsorption amount per unit volume, the gas adsorption amount per unit weight, and the gas adsorption amount per unit weight of the MOF were all higher. The evaluation results of the uniformity and gas adsorption of the MOF in the samples according to Examples 1 to 7 in comparison with Comparative Example 4 can be considered as follows. That is, since the first raw solution or the second raw solution was not dried after impregnation, it is considered that the solid content of each raw solution did not migrate to the surface of the base sheet during drying. In addition, it is considered that the reaction of forming the MOF proceeded smoothly without metal ionization being hindered by the solidification of the solute in the first raw solution or the second raw solution due to drying.
[0073] In all of Examples 1 to 7, the gas adsorption amount per unit volume, the gas adsorption amount per unit weight, and the gas adsorption amount per unit weight of the MOF were all greater than in Comparative Example 5 below, which also used ELM-11 as the MOF. This is believed to be because the MOF was able to exert its inherent gas adsorption function without being covered with resin. Furthermore, in all of Examples 1 to 7, the maximum bending stress was smaller, the gaps in the packing evaluation were smaller, and the Gurley air permeability was smaller than in Comparative Example 5 below. This is believed to be due to the fact that the resin was not adversely affected by melting.
[0074] In all of Examples 8 to 10, the gas adsorption amount per unit volume and the gas adsorption amount per unit weight were both greater than those in Comparative Example 6 below, which also used ZIF-8 as MOF. This is because the content ratio of MOF in all of Examples 8 to 10 was 80% or more, and it is believed that better gas adsorption performance was obtained in each sample.
[0075] [Table 1]
[0076] [Table 2]
[0077] (Comparative Examples 1 to 6) Next, composite sheet samples according to Comparative Examples 1 to 6 were prepared under the conditions shown in Table 3. Moreover, for each sample, the same analysis and evaluation as in Examples 1 to 10 were carried out. Table 4 shows the analysis and evaluation results for each sample. Below, Comparative Examples 1 to 6 will be described in detail. In Comparative Examples 1 to 5, ELM-11 was used as the MOF, similar to Examples 1 to 7. In Comparative Example 8, ZIF-8 was used as the MOF, similar to Examples 8 to 10.
[0078] Comparative Examples 1 to 3 In Comparative Examples 1 to 3, the same nonwoven fabric as in Example 1 was used as the sheet substrate. In Comparative Examples 1 and 2, instead of steps S02 to S04 according to the above embodiment, the sheet substrate was impregnated with a binder solution (water-soluble binder: polyvinyl alcohol (PVA), solid content 20%). Then, previously prepared MOF particles (average particle size 5 μm) were dispersed on both sides of the sheet substrate so as to obtain the MOF content ratio shown in Table 4. Then, after pressing at room temperature, a heat treatment was performed at 100° C. for 2 hours. In Comparative Example 3, instead of steps S02 to S04 according to the above embodiment, a paint containing MOFs prepared in advance was applied to both sides of a sheet substrate, and then heat treatment was performed at 100° C. for 2 hours. The composition of the paint containing MOFs used in Comparative Example 3 is as follows: Average particle size of MOF: 5μm Binder: Water-soluble PVA MOF / binder ratio: 1 / 1 Solvent: Deionized water Solid content: 20% In all of Comparative Examples 1 to 3, the fibers in the composite sheets maintained their original shape.
[0079] In none of the composite sheet samples according to Comparative Examples 1 to 3 was the MOF directly supported on the fiber surface, and in all samples, the MOF surface was partially covered by dissolution of the sheath of the core-sheath fiber or contact with the binder.
[0080] Comparative Example 4 In Comparative Example 4, a porous substrate in which glass fibers were fixed in a sheet shape using a binder was used as the sheet base material. As in the manufacturing process of the composite sheet according to the above comparative configuration example, the sheet base material impregnated with the first raw material solution in step S02 was dried, and then the sheet base material was impregnated with the second raw material solution in step S03. The number of steps S02 to S04 was three, including the step of drying the sheet base material between steps S02 and S03. In Comparative Example 4, the fibers in the composite sheet maintained their shape.
[0081] Comparative Example 5 In Comparative Example 5, a nonwoven fabric made of PE fibers was used as the sheet substrate. Instead of steps S02 to S04 according to the above embodiment, pre-produced MOF particles (average particle size 5 μm) were sprayed on both sides of the sheet substrate. In the obtained sample, the PE fibers, which were composed only of PE with a low melting point, dissolved due to heat treatment, and no longer maintained their fibrous form, becoming a sheet in which the MOF was coated with polyethylene resin.
[0082] Comparative Example 6 The sample according to Comparative Example 6 differs from the above-described embodiment in that the content of MOF is less than 80 mass %.
[0083] [Table 3]
[0084] [Table 4]
Claims
1. A composite sheet in which a metal organic framework is dispersed in a sheet base material composed of fibers, The metal-organic framework is supported on the surface of the fiber, a ratio of the mass of the metal organic framework to the total mass of the composite sheet is 80 mass% or more; a surface coverage rate of the fibers constituting a central portion of the composite sheet in a thickness direction by the metal-organic framework is 60% or more; The surface exposure rate of the metal organic framework is 50% or more. Composite sheet.
2. The fibers include organic fibers. The composite sheet of claim 1 .
3. The fibers include hydrophilic fibers and hydrophobic fibers. The composite sheet according to claim 1 or 2.
4. The maximum bending stress is 5 MPa or less. The composite sheet according to claim 1 or 2.
5. The inter-fiber distance of the sheet base material in the composite sheet is 1 μm or more and 1000 μm or less. The composite sheet according to claim 1 or 2.
6. A method for producing a composite sheet in which a metal organic framework is supported on a sheet base material composed of fibers, comprising the steps of: A first raw material solution containing one of metal ions and organic ligands that are raw materials for the metal organic framework, and a second raw material solution containing the other are prepared; impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; Drying the sheet base material impregnated with the second raw material solution; The dried sheet substrate is subjected to a heat treatment, Before the heat treatment, the ratio of the mass of the metal organic framework to the mass of the entire composite sheet after the heat treatment is 80 mass% or more. impregnating the sheet substrate with the first raw material solution; impregnating the sheet base material with the second raw material solution before the first raw material solution impregnated into the sheet base material dries; The sheet base material impregnated with the second raw material solution is dried. Repeat the process A method for manufacturing a composite sheet.
7. One of the first raw solution and the second raw solution contains 30% by mass or more and 99% by mass or less of water, and the other contains 30% by mass or more and 99% by mass or less of an organic solvent. A method for producing the composite sheet according to claim 6.
8. At least one of a time for impregnating the sheet base material with the first raw material solution and a time for impregnating the sheet base material with the second raw material solution is 0.01 minutes or more and 30 minutes or less. A method for producing the composite sheet according to claim 6 or 7.
9. The fibers include organic fibers. A method for producing the composite sheet according to claim 6 or 7.
10. The fibers include hydrophilic fibers and hydrophobic fibers. A method for producing the composite sheet according to claim 6 or 7.
Citation Information
Patent Citations
Composite solid electrolyte membrane based on Cu (BDC) MOF multi-stage structure and preparation method thereof
CN112002938A
Fibrous structures containing immobilized particulate matter and method of making same
JP1996503272A
Filtering medium for air filter and its production method
JP2005034693A
Porous coordination polymer
JP2016193957A
Composite, manufacturing method of composite, adsorbent and purifying method of liquid
JP2019018175A